OP0154 Altered lymph node stromal cells during the earliest phases of rheumatoid arthritis. (15th June 2017) - Ospelt, C; Karouzakis, E; Hähnlein, J; Semmelink, JF; Gay, RE; Tak, PP; Gerlag, DM; Gay, S; Baarsen, LG van
Abstract : Background: Lymph node stromal cells (LNSC) play a crucial role in shaping the immune response and maintaining peripheral tolerance. We developed an experimental model for studying the functional capacities of human LNSC during the earliest phases of RA and compared their cellular and molecular characteristics to LNSC from healthy volunteers. Methods: ACPA+ RA patients (n=24), ACPA+ RA-risk individuals (n=23) and seronegative healthy controls (n=14;HC) underwent ultrasound-guided inguinal lymph node biopsy. Human LNSCs were isolated and expanded in vitro for cellular (flow cytometry), molecular (methylome, transcriptome and microRNA) and functional (contraction) analyses. Results: RNA sequencing was performed on LNSC of HC (n=5), ACPA+ RA-risk individuals (n=6) and ACPA+ RA patients (n=4). Of interest, LNSC from ACPA+ RA-risk individuals and ACPA+ RA patients were more similar to each other compared with HC. Pathway analysis of commonly increased genes in RA (-risk) LNSC showed, among others, significant enrichment of pathways affecting actin cytoskeleton, focal adhesion and cell junction. DNA methylation (Illumina HumanMethylation450 array) analyses revealed 459 differentially methylated CpG sites (DMS) in LNSC from ACPA+ RA patients (n=5) versus HC (n=4), 504 DMS between ACPA+ RA-risk individuals (n=3) versus HC and 665 DMS when comparing RA patients with RA-risk individuals (delta β-value >0.1, p<0.05). 34 DMS were different in both RA and RA-risk LNSC compared to healthy LNSC. 80% of these DMS were significantly hypomethylated and associated with antigen processing and presentation (HLA-DRB1), immune response and regulation of actin cytoskeleton. Accordingly, in a gel contraction assay LNSC from ACPA+ RA-risk individuals and RA patients showed impaired collagen contraction compared to healthy LNSC. Healthy LNSC (n=5) covered 26.5% +/-2.5 of the well, while RA-risk (n=4) and RA (n=5) LNSC only covered 33.9% +/-5.9 and 30.6% +/-6.5. Conclusions: This data point towards alterations in the cytoskeleton and antigen-processing and presentation in LNSC from ACPA+ RA-risk individuals and RA patients. Further studies are required to investigate the influence of this LNSC abnormality on immune responses. Disclosure of Interest: C. Ospelt: None declared, E. Karouzakis: None declared, J. Hähnlein: None declared, J. Semmelink: None declared, R. Gay: None declared, P. Tak Employee of: GSK, D. Gerlag Employee of: GSK, S. Gay: None declared, L. van Baarsen: None declared